2009
DOI: 10.1093/occmed/kqp169
|View full text |Cite
|
Sign up to set email alerts
|

Managing long-term worklessness in primary care: a focus group study

Abstract: Background Evidence suggests that overall the benefits of work are greater than the harmful effects of long-term unemployment and prolonged sickness absence. General practitioners (GPs) often feel that work and health-related issues extend beyond their role. There is a paucity of research that focuses on GPs' attitudes to the management of long-term worklessness. AimsTo explore GPs' perceptions of the management of individuals in receipt of long-term incapacity benefits and their attitudes to UK government fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…Several studies have shown that certification rates are higher for patients presenting with psychological problems, and the condition seems to generate greater sympathy from GPs (6,9,17 -20). There is little evidence to support the therapeutic role of abstaining from work for those with mental health problems (21,22). However, patients have reported that stress and depression have a high impact on the ability to work, and thus…”
Section: Reasons For Psychological Related Sickness Certifi Cationmentioning
confidence: 99%
“…Several studies have shown that certification rates are higher for patients presenting with psychological problems, and the condition seems to generate greater sympathy from GPs (6,9,17 -20). There is little evidence to support the therapeutic role of abstaining from work for those with mental health problems (21,22). However, patients have reported that stress and depression have a high impact on the ability to work, and thus…”
Section: Reasons For Psychological Related Sickness Certifi Cationmentioning
confidence: 99%
“…Personally addressing certain health‐related barriers was viewed by most Personal Advisers as a legitimate task to perform. However, understanding the impact of a claimants’ health condition and identifying suitable forms of work can be a challenging task, and healthcare professionals have struggled to achieve this (Cohen, Marfell, Webb, Robling, & Aylward, ). Importantly, there are many differences between the role of the Personal Adviser and a healthcare professional.…”
Section: Discussionmentioning
confidence: 99%
“…However, workplace health appears to be an area of practice where GPs report a lack of knowledge, confidence and training in handling work issues with patients (Roope et al ., 2009; Money et al , 2010). Changes to the system involve challenges for the GP, particularly in the areas of long-term worklessness and rehabilitation (Cohen et al , 2012). Our results support previous evidence that suggests that GPs may avoid research in this complex area because of such issues.…”
Section: Discussionmentioning
confidence: 99%